Gate‐Controlled Quantum Dots Based on 2D Materials. Issue 6 (14th April 2022) - Jing, Fang‐Ming; Zhang, Zhuo‐Zhi; Qin, Guo‐Quan; Luo, Gang; Cao, Gang; Li, Hai‐Ou; Song, Xiang‐Xiang; Guo, Guo‐Ping
Abstract: 2D materials are a family of layered materials exhibiting rich exotic phenomena, such as valley‐contrasting physics. Down to single‐particle level, unraveling fundamental physics and potential applications including quantum information processing in these materials attracts significant research interests. To unlock these great potentials, gate‐controlled quantum dot architectures have been applied in 2D materials and their heterostructures. Such systems provide the possibility of electrical confinement, control, and manipulation of single carriers in these materials. In this review, efforts in gate‐controlled quantum dots in 2D materials are presented. Following basic introductions to valley degree of freedom and gate‐controlled quantum dot systems, the up‐to‐date progress in etched and gate‐defined quantum dots in 2D materials, especially in graphene and transition metal dichalcogenides, is provided. The challenges and opportunities for future developments in this field, from views of device design, fabrication scheme, and control technology, are discussed. The rapid progress in this field not only sheds light on the understanding of spin–valley physics but also provides an ideal platform for investigating diverse condensed matter physics phenomena and realizing quantum computation in the 2D limit. Abstract : Gate‐controlled quantum dots provide access to electrically manipulating individual charge carriers. This paper reviews recent advances of etched and gate‐defined quantum dots based on 2D materials. Such nanostructures offer promising platforms to study various quantum degrees of freedom at single‐particle level, showing great potential towards the realization of solid‐state quantum computation in 2D materials.